Toward an understanding of the systematics and evolution of the genus Acrapex Hampson, 1894 (Lepidoptera: Noctuidae: Apameini: Sesamiina): molecular phylogenetics of the genus and review of the species-rich Acrapex aenigma group. Issue 1 (2nd January 2020) - Le Ru, Bruno; Capdevielle-Dulac, Claire; Musyoka, Boaz K.; Pallangyo, Beatrice; Njaku, Mohamedi; Goftishu, Muluken; Assefa, Yoseph; Chipabika, Gilson; Conlong, Desmong; Ong'amo, George; Barbut, Jérôme; Kergoat, Gael J.
Summary: With a species count reaching almost 100 species, the genus Acrapex is the most diverse genus of sesamiine stemborers (Lepidoptera: Noctuidae: Noctuinae: Apameini: Sesamiina). Acrapex species are mostly distributed in the Afrotropics and consist of several large clades corresponding to distinct species complexes. In this study, 45 morphologically similar species of Acrapex from sub-Saharan Africa are reviewed, including 22 new species that are described: Acrapex alemura n. sp ., A. barnsi n. sp ., A. capelongo n. sp ., A. congoensis n. sp ., A. elgona n. sp ., A. elisabethiana n. sp ., A. eucantha n. sp ., A. grandis n. sp ., A. igominyi n. sp ., A. inexpectata n. sp ., A. ketoma n. sp ., A. lilomwi n. sp ., A. mafinga n. sp ., A. makete n. sp ., A. marungu n. sp ., A. mazoe n. sp ., A. mlanje n. sp ., Acrapex muchinga n. sp ., A. ngorongoro n. sp ., A. obscura n. sp ., A. ruiru n. sp . and A. wittei n. sp . Supplemental descriptions for previously described species are provided as well. These 45 species are assigned to the newly defined Acrapex aenigma species group. We also conduct molecular phylogenetic analyses and molecular species delimitation analyses on a multi-marker (four mitochondrial and two nuclear genes) molecular dataset encompassing 304 specimens (including 256 Acrapex specimens from 54 species of which 16 species belong to the A. aenigma group). Molecular phylogenetics analyses recover well-supported relationships within Acrapex and support the monophyly of the newly defined group. Results of molecular species delimitation analyses are mostly congruent and tend to corroborate the status of the sampled Acrapex species. Consistent with what has been previously found in other studies, the comparison of results from distinct methods and settings for molecular species delimitation analyses allows us to assess species boundaries with more confidence.